Clinical Profile of Unstable Angina/ NSTEMI Patients Presenting With Fragmented QRS- A Hospital Based Observational Study - Yadav, Ashwani Kumar; Mahajan, Kunal; Bansal, Vivek (International Journal of Innovative Research in Medical Science, 2016)
Electrocardiographic signs of unstable angina/non–ST elevation myocardial infarction (NSTEMI) are nonspecific. The utility of ST-segment and T-wave changes is limited and diagnosis of NSTEMI during acute coronary syndromes (ACS) depends mainly on cardiac biomarker levels. So clinicians have to depend on various non invasive and invasive studies, such as echocardiography, nuclear imaging, or cardiac catheterization, to confirm the presence of obstructive coronary artery disease (CAD).Fragmented QRS complex is a lesser known entity. This marker of myocardial injury may often be the only electrocardiographic marker in patients with NSTEMI. The prognostic significance of fragmented QRS is comparable to that of ST-segment depression and T-wave inversion. We postulated that the presence of fQRS might be associated with a poorer outcome in patients of acute coronary syndrome. The study included 150 consecutive patients of acute coronary syndrome. Fragmented QRS developed in 50 patients (GROUP A) while remaining 100 patients had no fragmented QRS during hospital stay (GROUP B). Both groups were followed up for a month. Group A had a higher disease burden and a poorer outcome in comparison to group B. This may prompt clinicians to act differently with more interventional approach immediately in patients of acute coronary syndrome who develop fragmented QRS on electrocardiogram, although this fact needs to be validated in large randomized trials.